(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
A great variety of iron oxides are present in soils and paleosols; these can be inherited from the parent material or formed during pedogenesis. Different authors have analyzed magnetic properties of soils and they are mainly associated with climate, topography, soil drainage, characteristics of the parent material or the occurrence of fires. Besides, considering that current climatic and environmental characteristics are more accurately known than such conditions in the geological past, it is estimated that the application of these techniques in soils could help to establish the framework for the study of paleosols through its magnetic properties. This contribution is part of a wider research, which tends to differentiate the soils of the Pampean region based on their magnetic properties. Four soil profiles from central Buenos Aires province are analyzed from the environmental magnetism perspective (Fig. 1) and are compared with the results obtained by several authors in the north and south of the same province. The comparison tends to develop a regional magnetic model for the Late Pleistocene- Holocene loess deposits and loess-derived soils in the Pampean region. The soils of the study area are developed from loess deposits of Late Pleistocene-Holocene (Las Áni- mas Formation), but they are also controlled by the presence of a regional calcareous crust found below of Las Ánimas Formation, affecting loessoid fluvial sediments that constitute another lithostratigraphic unit, called Vela Formation (Middle Pleistocene). The current climate is humid to subhumid, mesothermal, with a slight hydric excess, with an average annual rainfall of 838 mm and annual average temperature of 13,6ºC; potential evapotranspiration was calculated at 712 mm/year and real evapotranspiration at 694 mm/year. The soils in the area correspond to the Mollisol order, and as the moisture regime is mainly udic across the region, the suborder is Udoll (Soil Survey Staff, 2014). Taking into account the surveys carried out by Pazos (2014) and INTA (National Institute of Agricultural Technology) in support of the field descriptions (Table 1 - 4), the analysed soils profiles were tentatively classified at the subgroup level of Soil Taxonomy. Two Typic Argiudolls (P1 and P4), a Petrocalcic Hapludoll (P2) and a Typic Hapludoll (P3) were recognized. Whereas the Typic Argiudolls correspond to “zonal” soils, the rest are “intrazonal” soils, in which the development of the Petrocalcic Hapludoll is conditioned by a shallow duricrust and the Typic Hapludoll by a relatively high slope. Samples of each soil horizon were extracted for analysis by thermogravimetric techniques, which allowed loss on ignition determination at 550 and 1000ºC, and the measurement of magnetic parameters, which included magnetic susceptibility, isothermal remanent magnetization and anhysteric remanent magnetization. Figure 3 shows the varia- tion of the determined parameters as depth-functions for each soil profile, whereas the analyses related to the lithostratigraphic units and soil horizons are shown in the histograms of figures 4 to 6. Besides, the greater amounts of measurements of magnetic susceptibility (?bf) make it possible a more detailed analysis of this parameter (Fig. 5b). The coercivity of remanence (Hcr) and S-ratio (Coef. S) values, as well acquisition of isothermal remanent magnetization curves design (Fig. 7), are consistent with the magnetic signature of ferrimagnetic species. According to Peters and Dekkers’ graph (2001), the samples correspond to magnetite-titanomagnetites- maghemite (Fig. 8a). These data are consistent with those indicated for other soils with loessic parent materials of the Pampean region where it has been determined by different ways that the detrital magnetic composition mainly corresponds to titanomagnetites with low titanium. According to King et al. (1982) (Fig. 9) the magnetic grains would be less than 1 micron diameter, and are considered of single domain (SD). Samples of horizons A and B present smaller magnetic particles than the parent materials (C horizons). Besides, the frequency- dependent susceptibility indicates that the relative presence of ultrafine particles (SP) increase in the solum horizons, in which there is also recorded, taking into account the inter-parametric relations, an increase of fine magnetic particles (SD and SD- SP limit) (Fig. 10). Finally, the decline of Hcr values at the A and B horizons would indicate that the magnetic particles of pedogenetic origin formed in these horizons have low coercivity (Fig. 8b). An aspect to remark is that the magnetic concentration in the parent material of the analyzed soils presents differences between the soils of north and south of the same province (Fig. 11). It is lower in the north and higher in the south; this would be related to the sediment distribution mechanisms at the regional level and the sources areas, corro- borating the utility of magnetic parameters for provenance analyses. In our case, it seems that the deposits register the highest magnetic concentrations as closer to the source area, in the flood plains of the Colorado and Negro Rivers, but in the north of Buenos Aires is also possible a contribution of poorly magnetic sediments of a cratonic origin related to the Paraná River basin. In respect to the pedogenetic magnetic signal, the behavior corresponds to the so-called magnetic enhancement, linked to an enrichment of ultrafine (SP) to fine (SD) magnetic particles by the effect of pedogenesis. The same behavior was determined in soils in the south of the province of Buenos Aires; while in the north of this province the opposite (depletion) dominates. Such difference seems to be related to the time of permanence of the water in the soil, an aspect that integrates climate, topography and hydraulic characteristics of the material. It is considered that a prolonged permanence of water in the soil favors the loss of lithogenic magnetite by oxidation. On the other hand, the alternation of wetting-drying cycles of short duration in a predominance of aerobic conditions, leads to the neoformation of magnetite (and/or maghemite) particles, as well as a greater conservation of the detrital magnetite.